Optimizing The Role of Zakat and Wakaf in Promoting National Economic Growth: Analytic Network Process (ANP) Method Approach - Islamy, Robithoh Alam; Hannase, Mulawarman (Journal of Islamic Economic Laws, 2021)
This study aims to determine the criteria and aspects of optimizing the role of zakat and infaq. This research’s further objective is to build a model that can be used to determine criteria and priority aspects to become input for related parties to improve the role of zakat and waqf. This study combines descriptive qualitative and quantitative research using the Analytic Network Process (ANP) method. In building models and calculations, experts are involved in producing results following conditions in the field. This study indicates that zakat and waqf have played a role in encouraging national economic growth. Aspects that become alternatives in optimization are aspects of policy/legality/institutional, technical aspects of operations/databases, human resources/management aspects, aspects of auditing/control, socialization/community literacy, and cooperation aspects. The criteria used in selecting alternatives are effective criteria (collection and distribution) and efficient criteria (cheap, fast, and applicable). The ANP model connects alternatives and criteria and calculates that the order of priority from the highest to the lowest is 1. Policy, Legality, and Institutions (47.28%); 2. Human Resources/Management Aspects (13.94%), 3. Socialization Aspects (12.66%); 4. Cooperation Aspects (12.54%); 5. Operational/Database Technical Aspects (8.27%) and; 6. Audit/Control Aspects (5.29%).